Digital Archives Management in the Public Sector: A Bibliometric Study - Damanik, Marudur Pandapotan; Cahyarini, Benedicta Retna; Arsalam, Syakib; Gusparirin, Rori; Wulan, Diah Retno; Cahyarida, Ilham; Ahad, Madya Putra Yaumil; Hamjen, Hilarion (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This study examined development trends in digital archives management within government agencies using a bibliometric approach, covering the period from 2001 to 2023. The bibliometric approach was applied to examine publication patterns from 170 articles sourced from the Scopus database, filtered based on specific criteria. The analysis integrates qualitative and quantitative assessments to identify influential works and emerging themes in the field. The study revealed a notable growth in scholarly interest, with publications increasing from 10 in 2022 to 17 in 2023. The United States emerged as the leading contributor in both publication output and citation impact. Among journals, Government Information Quarterly (355 citations), The Electronic Library (144 citations), and Records Management Journal (180 citations) were identified as highly influential. Keyword network analysis highlighted key research directions centered on leveraging technology for digital archives management. Dominant themes included “records management,” “e-government,” and “blockchain,” reflecting a focus on optimizing archival practices and ensuring secure, interoperable systems. Future research should explore integrating blockchain with e-government frameworks to enhance records management security and developing interoperable electronic archive systems. The study underscores the importance of a collaborative, multidisciplinary approach involving archivists, technologists, and policymakers to foster innovation and address challenges in digital archives management.